Simple fire model for comparative studies of critical conditions during combustion of chosen polymer materials - Marek Konecki; Marzena Półka (Journal of Civil Engineering and Management, 2009)
The time taken to evacuate space inside a building (required time for evacuation) must be shorter than the time for the environment in that space to become life threatening (available safe egress time ‐ ASET). That time is the time, when certain tenability limits of smoke filling, toxicity and thermal influence of the building environment are exceeded. As a consequence of lost visibility in smoke, people loose their orientation, and consequently evacuation is slowed down or becomes impossible. In such conditions inhaling of an excessive volume of toxins may lead to loss of consciousness or death. In the paper are discussed the influences of visibility through a smoke layer (or smoke obscuration) and concentration of toxic products of combustion on ASET, in well ventilated fires. Apart from the visibility range, also CO and CO2 concentrations have been chosen for the analysis. The given simple formulas show the dependency of rate of combustion and yields of smoke and toxic species on visibility reduction rate and increasing of concentration of toxic products evolved during combustion of selected materials. Epoxy materials were used for the analysis: pure Epoxy material 561 and epoxy with the following admixtures: MoO3, Roflam P and Melamine, as well as 2 types of polyurethane form.